UV - Sun light Photocatalytic and photoluminescence Studies of Rare-Earth-Doped (Sm3+) MgO nanopowders by Aloe Vera gel. (2017) - Anil Kumar, M.R.; Nagaswarupa, H.P.; Prashantha, S.C.; Channakeshavalu, K.; Anantharaju, K.S.; Nagabhushana, H.; Sharma, S.C.; Vishnu Mahesh, K.R.
Abstract: Sm3+ doped (0.1- 5mol %) MgO nanoparticles (NPs) were synthesized by a facile bio mediated combustion route by using Aloe Vera gel. The obtained products were characterized by PXRD, FTIR, DRS and SEM. PXRD patterns show typical peak at 2 value 37.02, 42.88, 62.33, 7.76 and 78.57which corresponds to hexagonal cubic structure of MgO (JCPDS card no. 4 - 829). The crystallite size calculated from Scherrer's formula was found to be in the range 12-30 nm. SEM images clearly reveal that irregular, pours and agglomerated morphologies. The optical band gap decreaces from 5.23 eV to 5.00 eV it is confirmed by DRS. The PL properties of Sm3+ doped MgO under ∼378 nm excitation was studied in order to investigate the possibility of its use in display applications. Further, the influence of Sm3+ ion on MgO matrix was investigated for the PC decolorization of Malachite green.